The “Reading the Mind in Films” Task: A Pilot Study on Complex Emotion and Mental State Recognition for the Italian Adaptation in Adults with and Without Autism Spectrum Conditions - Raffaele Simone Scuotto; Sofia Bonfanti; Paola Ricciardelli (Brain Sciences)
Background/Objectives: The present pilot study tested and reports the Italian adaptation of the Reading the Mind in Film test (RMF), an ecological test for assessing, in Italian adults with and without Autism Spectrum Condition (ASC), complex emotion and mental state recognition in natural settings and everyday situations. Method: A sample of young adults with Autism Spectrum Condition (with ASC; n = 22), attending a filmmaking course at a post-diploma school (Scuola Futuro Lavoro) took part in the study and was compared with a control group of neurotypical university students (without ASC; n = 22). All participants underwent individual testing and completed the Italian version of the Autism Questionnaire before performing the Italian version of both the RMF task and the Reading the Mind in the Eyes Test (RMET). The latter, widely used to evaluate the ability to detect what someone else is thinking or feeling from the eye region. Results: The findings of the control group were in line with the original study, demonstrating the validity and reliability of the translation and the dubbing procedure of the RMF test. However, no main significant differences in performance were found between the two groups. Conclusions: Such results suggest that taking a course in film and video making may have helped the autistic students learn how to recognize mental states.